1996
DOI: 10.1016/0361-9230(96)00046-9
|View full text |Cite
|
Sign up to set email alerts
|

Effects of the GABAB antagonist CGP 35348 on sleep-wake states, behaviour, and spike-wave discharges in old rats

Abstract: The GABA, antagonist CGP 35348 was intraperitoneally given in doses of 100, 300, and 900 mglkg to old rats. These rats were earlier chronically provided with EEG and EMG electrodes. Sleep recordings based on visual inspection of EEG and EMG recordings were made for 3 h post injection, and spontaneous behaviour in the recording cage was additionally observed. With 100 and 300 mglkg, the drug produced an increase in the duration of REM sleep compared to the saline-injected control group. The REM sleep latency wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0

Year Published

1998
1998
2010
2010

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(21 citation statements)
references
References 31 publications
1
20
0
Order By: Relevance
“…Interestingly, early studies performed in both GAERS and WAG/Rij rats found that injecting GABA B receptor antagonists either into the thalamus or systemically, blocked absence seizures (Liu et al, 1992;Snead, 1996;Puigcerver et al, 1996). These data have been interpreted as reflecting the ability of GABA B receptor antagonists to reduce slow hyperpolarizing IPSPs (and thus their ability to de-inactivate low-threshold Ca 2+ conductances) in thalamocortical relay cells (Steriade et al, 1993).…”
Section: Changes In Paired-pulse Depression In Wag/rij Somatosensory mentioning
confidence: 99%
“…Interestingly, early studies performed in both GAERS and WAG/Rij rats found that injecting GABA B receptor antagonists either into the thalamus or systemically, blocked absence seizures (Liu et al, 1992;Snead, 1996;Puigcerver et al, 1996). These data have been interpreted as reflecting the ability of GABA B receptor antagonists to reduce slow hyperpolarizing IPSPs (and thus their ability to de-inactivate low-threshold Ca 2+ conductances) in thalamocortical relay cells (Steriade et al, 1993).…”
Section: Changes In Paired-pulse Depression In Wag/rij Somatosensory mentioning
confidence: 99%
“…A series of pharmacological results suggests that GABA B receptors play a critical role in the genesis of SW discharges in rats, because GABA B agonists exacerbate seizures whereas GABA B antagonists suppress them (Hosford et al, 1992;Snead, 1992;Puigcerver et al, 1996;Smith and Fisher, 1996). The anti-absence drug clonazepam seems to act by diminishing GABA B -mediated IPSPs in thalamocortical (TC) cells, reducing their tendency to burst in synchrony (Huguenard and Prince, 1994a;Gibbs et al, 1996).…”
Section: Abstract: Computational Models; Thalamus; Cerebral Cortex; mentioning
confidence: 99%
“…In addition, as proposed for thalamocortical relay cells [37] , an increased release of GABA should activate postsynaptic GABA B receptors, thus producing robust hyperpolarizing IPSPs that contribute to de-inactivate low-threshold Ca 2+ conductances, which in turn facilitate rhythmic bursting. In line with this view, injecting GABA B receptor antagonists, either into the thalamus or systemically, blocks absence seizures in both GAERS and WAG/Rij rats [38][39][40] .…”
Section: Discussionmentioning
confidence: 65%